Exploring the influence of leadership styles on cooperation and contribution in public goods games: a comparative study of Laissez-Faire, authoritarian, and democratic approaches - Ooi, Yuan Phing (Nanyang Technological University, 2023)
In behavioural economics, much research using the public goods game has found that public goods are able to be supplied without free riding as participants are often not as self-interested and rational as predicted by traditional economics, especially with intervention. We propose that leadership, which aims to guide and influence members towards a certain goal, may be able to aid the contribution in the public goods game by facilitating the achievement of the optimal outcome of the game. To investigate this, we conducted a modified public-goods game using z-tree to investigate three different leadership styles, namely Laissez-Faire, Democratic and Authoritarianism, on efficiency and equality of earnings of the game. Overall, we find that leadership plays an important role in improving efficiency and equality. Specifically, democratic and authoritarian styles perform significantly better than LF, but all three styles perform better than the control condition. The research findings can be useful in providing great insights to policy and management leaders, thus promoting greater collaboration and a better outcome.